14p+q-6p+16q=

Simple and best practice solution for 14p+q-6p+16q= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14p+q-6p+16q= equation:


Simplifying
14p + q + -6p + 16q = 0

Reorder the terms:
14p + -6p + q + 16q = 0

Combine like terms: 14p + -6p = 8p
8p + q + 16q = 0

Combine like terms: q + 16q = 17q
8p + 17q = 0

Solving
8p + 17q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-17q' to each side of the equation.
8p + 17q + -17q = 0 + -17q

Combine like terms: 17q + -17q = 0
8p + 0 = 0 + -17q
8p = 0 + -17q
Remove the zero:
8p = -17q

Divide each side by '8'.
p = -2.125q

Simplifying
p = -2.125q

See similar equations:

| 4.8=9x | | -2(1-2m)=-(-4+2m) | | -5m+7-5+1+m=0 | | 3(d+8)=21 | | 5.55567973144b+2000=7b+500000000 | | -9x-1=19 | | 8ax-y=3y+ax | | 4x^2-2y^2-9=o | | 2x-2/3x | | 7x+3-2x+5=0 | | -2(-2v^3-3+3u^2)= | | 3x^3-12x^2+8=0 | | -2(-2v^3-3+3v^2)= | | y=19x+5 | | 4(c-6)=7c | | 6+7c-5-8= | | 1.5x(-2)= | | -6(2k+8)-(3-8k)=-27 | | 2/3(x-18)=17 | | 2/5x1 | | -64x-6/50 | | 5y-8=9+4(y-5) | | 4c/3-2=8 | | 3(2d-1)+5=4(d+1) | | y=-3/2x-9 | | -3/4*-6 | | 2(6x-3)=-(6-12x) | | Sqrt(2y+13)=sqrt(5y+7) | | p^2=15-2p | | -2(w+11)=6 | | 2/3(9-2x)=-30 | | 13p^2+52=0 |

Equations solver categories